PEMBAGIAN WARISAN PADA MASYARAKAT ADAT BATAK TOBA (STUDI DI DESA MARTOBA KECAMATAN SIMANINDO KABUPATEN SAMOSIR) - Sidabutar, Menanti; Hasanah, Ulfia; ', Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Property (vermogen) is all rights and obligations that have people, who have value for money. Thus it can be said that inheritance law is part of the law of wealth. Inheritance law is the provisions that govern the fate of one's wealth after the owner dies. During his life man has wealth. The wealth will not be brought after the owner dies. The wealth will be distributed to those who are entitled to receive it that is the closest offspring of the deceased and or the person appointed to receive it. The deceased is called the heir, while the one who is entitled to receive the treasure is called the heir. In the Tapanuli community (